The edge of reason : a rational skeptic in an irrational world - Baggini, Julian (Yale University Press, 2016)
"Reason, long held as the highest human achievement, is under siege. According to Aristotle, the capacity for reason sets us apart from other animals, yet today it has ceased to be a universally admired faculty. Rationality and reason have become political, disputed concepts, subject to easy dismissal. Julian Baggini argues eloquently that we must recover our reason and reassess its proper place, neither too highly exalted nor completely maligned. Rationality does not require a sterile, scientistic worldview, it simply involves the application of critical thinking wherever thinking is needed. Addressing such major areas of debate as religion, science, politics, psychology, and economics, the author calls for commitment to the notion of a "community of reason," where disagreements are settled by debate and discussion, not brute force or political power. His insightful book celebrates the power of reason, our best hope--indeed our only hope--for dealing with the intractable quagmires of our time"--